Overcoming challenges in the study of nitrided microalloyed steels using atom probe. - Xie, K; Breen, A; Yao, L; Moody, M; Gault, B; Cairney, J; Ringer, S (2012)
Nitrided steels are widely used in the engineering field due to their superior hardness and other attractive properties. Atom probe tomography (APT) was employed to study two Nb-microalloyed CASTRIP steels with different N contents. A major challenge of using APT to study this group of materials is the presence of tails after Fe peaks in the mass spectra, which overestimates the composition for alloying elements such as Nb and Cu in the steels. One important factor that contributes to the tails is believed to be delayed field evaporation from Fe²⁺. This artefact of the mass spectrum was observed to be the most severe when voltage pulsing was used. The application of laser pulses with energy ranging from 0.2 to 1.2 nJ successfully reduced the tails and lead to better compositional measurement accuracy. Spatial resolution in the z-direction (along the tip direction) was observed to be less affected by changing laser energy but deteriorates in x-y direction with increasing laser energy. This investigation suggests that pulsed-laser atom probe with ∼0.4 nJ laser energy can be used to study this group of materials with improved mass resolution while still maintaining high spatial resolution.